FROM THE PAGES OF HISTORY TO CONTEMPORARY PERIODS: A STUDY OF INDIA-INDONESIA RELATIONSHIP (Lingua, 2018)
The relation between India and Indonesia is not new and it had dated back to the ancient period which is quite evident from the architectural remnants in Indonesia. The Indian traders had sailed through the South East Asian Nations and also been said to be spread of Sanskrit language in Indonesia. Not only that both Hinduism and Buddhism had been said to be spread from India to Indonesia. India had always shared a cordial relation with Indonesia, from the ancient period till the present days. Both had undergone a similar phrase of colonial rule and India had always supported Indonesia in her freedom struggle also during the Cold War era, both have followed the policy of Non Alignment of not joining any of the power blocs. The relation had grown since the end of the Cold War as India had started its’ Look East Policy (LEP) in 90’s to enhance its ties with its South East Asian neighbors. India has several ties and cooperation with Indonesia including economic, culture, defense, science and technology, environment etc. The ties have also enhanced during the recent years after India have adopted its Act East Policy (AEP). This policy have aim to foster growth through more cooperation and involvement in each other growth and development.Hubungan antara India dan Indonesia bukanlah hal baru dan telah kembali ke periode kuno yang cukup nyata dari sisa-sisa arsitektur di Indonesia. Pedagang India telah berlayar melewati negara-negara Asia Tenggara dan juga dikatakan menyebarkan bahasa Sanskerta di Indonesia. Tidak hanya agama Hindu dan Budha yang telah disebarkan dari India ke Indonesia. India selalu berbagi hubungan baik dengan Indonesia, dari periode kuno sampai sekarang. Keduanya telah mengalami perubahan yang sama dengan pemerintahan kolonial dan India selalu mendukung Indonesia dalam perjuangan kebebasannya selama era Perang Dingin, juga telah mengikuti kebijakan Non Alignment untuk tidak bergabung dengan blok kekuasaan manapun. Hubungan tersebut telah berkembang sejak berakhirnya Perang Dingin karena India telah memulai Look East Policy (LEP) atau Kebangkitan Bangsa Timur di tahun 90-an untuk meningkatkan hubungannya dengan negara-negara Asia Tenggara. India memiliki beberapa ikatan dan kerja sama dengan Indonesia termasuk ekonomi, budaya, pertahanan, sains dan teknologi, lingkungan dan lain-lain. Hubungan tersebut juga meningkat dalam beberapa tahun terakhir setelah India menerapkan Act East Policy (AEP) atau Kebijakan Pergerakan Timur. Kebijakan ini bertujuan untuk mendorong pertumbuhan melalui kerja sama dan keterlibatan dalam pertumbuhan dan perkembangan masingmasing.